Reading Antebellum New York Dailies Against the Grain: The Case of Almira C. Loveland - Murray, Laura (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2012)
This essay describes some of the challenges in understanding reading experiences associated with daily newspapers of the 1830s and 1840s. It then explores the scrapbook, poetry, and editorial career of New Yorker Almira Loveland, revealing how Loveland translated and transformed newspaper material from disposable to keepsake, man’s world to woman’s world, and sensational to sincere, ultimately returning it in new forms to the public sphere through her work as poet, editor, and activist. While her case is no doubt a special one, it suggests that the masculinist editorial bombast of these papers is not determinative of the modes of reading and mobilization they enabled, and it offers an invitation to imagine a diversity of reading experiences little documented in the archives.